2021
DOI: 10.1186/s12879-021-05945-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of interleukin 6 as a predictive factor for a severe course of Covid-19: retrospective data analysis of patients from a long-term care facility during Covid-19 outbreak

Abstract: Background Covid-19 is a disease with high morbidity and mortality among elderly residents of long-term care facilities (LTCF). During an outbreak of SARS-CoV-2 infection in the LTCF an effective screening tool is essential to identify the patients at risk for severe disease. We explored the role of interleukin 6 (IL-6) as a predictor for severe disease during the outbreak of Covid-19 in one LTCF in Slovakia. Methods We conducted a retrospective da… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
71
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 32 publications
(35 reference statements)
9
71
0
2
Order By: Relevance
“…However, the study performed on our patients indicates significantly higher concentrations of ferritin and IL-6 in patients with COVID-19 requiring intensive care comparing with those hospitalized in non-ICU departments. With our results, we confirm observations made by other groups showing that IL-6 allows distinguishing between severe and nonsevere COVID-19 [ 38 , 39 , 40 , 41 , 42 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the study performed on our patients indicates significantly higher concentrations of ferritin and IL-6 in patients with COVID-19 requiring intensive care comparing with those hospitalized in non-ICU departments. With our results, we confirm observations made by other groups showing that IL-6 allows distinguishing between severe and nonsevere COVID-19 [ 38 , 39 , 40 , 41 , 42 ].…”
Section: Discussionsupporting
confidence: 92%
“…The researchers’ analysis of the ROC curve showed that IL-6 is the most powerful predictor of hypoxemia. On the other hand, the concentration of IL-6 above 24 pg/mL indicated the development of hypoxemia with a sensitivity of 100% and a specificity of 88.9% [ 38 ]. Parviz et al found that the level of IL-6, the level of ferritin, and hematological parameters including WBC and the number of lymphocytes and neutrophils had a direct positive correlation with the concentration of hemoglobin [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of IL-6 has been suggested as a novel target for managing dysregulated host responses in patients with COVID-19 [21]. In the current study, the IL-6 values were decreased from values predictive of higher mortality due to COVID-19 > 24 pg/ml [22] to normal values which were maintained in the beta glucan groups only while it increased to values predictive of higher mortality in the control groups at day 30 (figure 4). The significant and steady decrease in IL6 and D-Dimer (figure 4 and 5) substantiate the anti-inflammatory and anti-coagulation benefits of beta glucans.…”
Section: Discussionsupporting
confidence: 47%
“…Inhibition of IL-6 has been suggested as a novel target for managing dysregulated host responses in patients with COVID-19 [3] . In the current study, the IL-6 values were decreased from values predictive of higher mortality due to COVID-19 > 24 pg/ml [25] to normal values which were maintained in the beta glucan groups only while it increased to values predictive of higher mortality in the control groups at day 30 ( Fig. 3 A).…”
Section: Discussionsupporting
confidence: 46%